Cover Feature: Titanium‐Catalyzed Hydroaminoalkylation of Ethylene (Chem. Eur. J. 10/2020). Issue 10 (21st January 2020) - Rosien, Michael; Töben, Iris; Schmidtmann, Marc; Beckhaus, Rüdiger; Doye, Sven
Abstract : Industrially important ethylene easily inserts into the titanium carbon bond of titanaaziridines to give titanapyrrolidines. Based on this reaction, this work reports the first examples of titanium‐catalyzed hydroaminoalkylation reactions of ethylene with secondary amines, which directly deliver α‐ethylated amines. The picture, created by Iris Töben, shows a simplified catalytic cycle in front of Oldenburg Palace, which is located in the city center of Oldenburg where the researchers developed the new reaction. More information can be found in the Communication by R. Beckhaus, S. Doye, et al. on page 2138 .